An Economic Analysis of Tax Amnesties. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1989)
Tax amnesties have frequently been justified as politically popular ways to generate increases in government revenue. This paper examines the circumstances under which amnesties are likely to have a beneficial impact on revenue collections. It concludes that, while in general it may be correct to impose a reduced penalty on individuals who voluntarily disclose tax evasion, short-lived amnesties of the type most frequently observed in practice are unlikely to generate significant revenue when judged against the potential danger of reducing future tax compliance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet